PENGARUH DANA PIHAK KETIGA, KECUKUPAN MODAL, KREDIT BERMASALAH, DAN SUKU BUNGA KREDIT TERHADAP PROFITABILITAS BANK (STUDI KASUS BANK BUMN YANG TERDAFTAR DI BEI TAHUN 2015-2022) - Iradati, Sulfa; Laras Asih, Dessy Novitasari (Journal MISSY (Management and Business Strategy), 2024)
Banking has a crucial function in maintaining economic stability. In 2020, BUlMN Bank's net profit decreased compared to the previous year, which was caused by the increase in the cost of reserves for impairment losses (CKPN) as an effort to anticipate the occurrence of bad loans. This research aims to examine the influence of Third Party Funds, Capital Adequacy, Problem Loans, and Credit Interest Rates on the Profitability of state-owned banks from 2015-2022. The method used in this research is descriptive quantitative. This research was conducted at state-owned banks registered on the IDX using total sampling or census techniques, where all population members were sampled. The data analysis technique used in this research is panel data regression analysis. The research results show that third-party funds, capital adequacy, problem loans, and credit interest rates simultaneously influence bank profitability. Partially, the Third Party Funds variable does not affect bank profitability, while the Capital Adequacy, Non-Performing Credit, and Credit Interest Rate variables partially affect bank profitability.